Pre‐race and race management impacts serum muscle enzyme activity in Australian endurance horses. (8th November 2021) - Buckley, Petra; Buckley, David J.; Freire, Rafael; Hughes, Kristopher J.
Abstract: Background: Marked increases in serum muscle enzyme activity can occur in endurance horses but the diagnostic certainty in predicting cases of myopathy is unclear. Improved understanding of horse management effects on serum muscle enzyme activity as markers of muscle health would assist interpretation of serum muscle enzyme activity and guide management to reduce myopathy risk. Objectives: To investigate associations between serum muscle enzyme activity and management factors in endurance horses. Study design: Cross‐sectional study. Methods: One hundred endurance horses competing in four endurance events (offering distances of 20‐120 km) in south‐eastern Australia were observed. Data were collected from official horse logbooks, pre‐and post‐race serum samples, an owner questionnaire of pre‐race and race management of horses and the Australian Endurance Riders Association results database. Multivariable linear regression modelling tested associations between management factors and serum muscle enzyme activity. Results: First leg speed, distance raced, number of rest days pre‐race, and pre‐race activity of aspartate aminotransferase (AST) and creatine kinase (CK) explained 47.3% of the variance in post‐race CK. As first leg speed increased by 1 km/h, CK activity increased by 25.8% (95% CI 11%‐35%). Race distances >80 km increased post‐race CK activity by 124% (95% CI 116%‐145%). Each additional pre‐race rest day increased post‐race CK activity by 30.5% (95% CI 11%‐42%). Modelling a 10% increase in pre‐race CK and pre‐race AST activity was associated with post‐race CK activity increasing by 7.3% (95% CI 3%‐14.4%) and 8.5% (95% CI 0.3%‐14.2%) respectively. Horses experiencing training distances >40 km and a greater number of rest days prior to race day developed increased pre‐race AST and CK activity respectively. Main limitations: Owner questionnaires may be subject to bias. Limited data were available to model ride terrain, horse fitness, ration detail and myopathy. Muscle biopsies were not used to confirm myopathy. Conclusions: Nearly half of the variation in post‐race CK activity observed can be attributed to management factors unrelated to myopathy, suggesting increased CK activity may not be pathognomonic for myopathy. We advise caution in relying solely on serum muscle enzyme activity for diagnosis of myopathy until the strength of association between CK and myopathy is further ascertained in future studies.